Nanoassembly of Polydisperse Photonic Crystals Based on Binary and Ternary Polymer Opal Alloys. Issue 10 (18th July 2016) - Zhao, Qibin; Finlayson, Chris E.; Schaefer, Christian G.; Spahn, Peter; Gallei, Markus; Herrmann, Lars; Petukhov, Andrei V.; Baumberg, Jeremy J.
Abstract : Ordered binary and ternary photonic crystals, composed of different sized polymer‐composite spheres with diameter ratios up to 120%, are generated using bending‐induced oscillatory shearing. This viscoelastic system creates polydisperse equilibrium structures, producing mixed opaline colored films with greatly reduced requirements for particle monodispersity, and very different sphere size ratios compared to other methods of nanoassembly.